Experiencia de interacción en trabajo de campo en una zona rural colombiana (2011)
ABSTRACT: The field work experience as a researcher with Ember Chamí Indians in the city of Jardín Antioquia, Colombia is shared. Work field implications, participants’ approach as individuals, groups or communities and societies. It tells specifically the introduction, field orientation, interaction with people, rule observation, daily, weekly and monthly life organization, as well as the roles and reciprocity relationships in the field.